APPLICATION OF PROJECT METHODS TO INCREASE INTERPERSONAL INTELLIGENCE OF EARLY AGE CHILDREN (CASE STUDY IN KARTIKA XIX-43 BRIGIF CIMAHI KINDERGARTEN) - deepprilla suhanda (IKIP Siliwangi Bandung, 2018)
Golden age is the golden age of child development which at the age of 0-6 years improves child interpersonal intelligence has been achieved at this time one of them through the implementation of the project method. The goal to be achieved through this research is to know and describe: 1). Early childhood interpersonal intelligence before applied project method in Kartika Kindergarten XIX-43 Brigif Cimahi 2). application of early childhood interpersonal intelligence through project method in Kartika XIX-43 Kindergarten Brigif Cimahi 3). Early childhood interpersonal intelligence after applied project method in Kartika XIX-43 Kindergarten Brigif Cimahi. This study uses qualitative research deskritif Source of this data are students in kindergarten KartikaXIX-43 Brigif Cimahi Tengah, School year 2017/2018, while the sample of the study amounted to 6 students into the case. The results showed that: 1) the initial condition to improve the interpersonal intelligence of the child by the teacher is still relatively monotonous and conventional in that it is associated with the limited work on the learning that is related to interpersonal intelligence 2) .process of learning the project method taken through the stages of learning the simple is not complicated and can be followed by the child. 3). The achievement of learning through project methods in certain forms has contributed to such improvements in interpersonal intelligence in general, especially when starting to cooperate with friends and division of tasks with other friends meningkast significantly. Based on the results of the discussion that has been described learning activities with the implementation of project methods is very positive impact on improving children's interpersonal intelligence in Kartika Kindergarten XIX-43 Central Cimahi Year 2017/2018. The result of obsevation of improvement of children interpersonal intelligence before and after implementing the project method showed optimal and significant development. Keywords: project method, interpersonal intelligen